A SIMPLIFIED ONTOLOGICAL ARGUMENT AND FICTIONAL ENTITIES. Issue 40 (9th April 2015) - Di Muzio, Gianluca
Abstract : This paper shows that a recent, simplified version of St. Anselm's proof of the existence of God has its flank open to Gaunilo's 'Lost Island' objection. Reformulating Anselm's line of reasoning in terms of the distinction between mediated and unmediated causal powers, as the simplified proof does, makes it harder for Anselm's supporters to refute the objection that the ontological argument absurdly entails the existence of all kinds of fictional entities.